2021
DOI: 10.3390/biomedicines9010041
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of Human Fibroblasts and Keratinocytes with Blue Light: Implications in Wound Healing

Abstract: In recent years, photobiomodulation (PBM) has been recognized as a physical therapy in wound management. Despite several published research papers, the mechanism underlying photobiomodulation is still not completely understood. The investigation about application of blue light to improve wound healing is a relatively new research area. Tests in selected patients evidenced a stimulation of the healing process in superficial and chronic wounds treated with a blue LED light emitting at 420 nm; a study in animal m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…These cells stimulated (i) an early inflammatory response; (ii) angiogenesis, thanks to the secretion of TNF-α [ 36 ]; and (iii) the response of fibroblasts that switched into myofibroblasts, which played a role in wound closure, evidenced by re-epithelialization and collagen deposition [ 36 , 37 , 38 , 39 , 40 , 41 ]. Therefore, together with our previous investigation [ 15 , 16 , 19 , 41 , 42 , 43 ], these results show that blue-LED-light irradiation induces a quicker healing process.…”
Section: Discussionsupporting
confidence: 85%
“…These cells stimulated (i) an early inflammatory response; (ii) angiogenesis, thanks to the secretion of TNF-α [ 36 ]; and (iii) the response of fibroblasts that switched into myofibroblasts, which played a role in wound closure, evidenced by re-epithelialization and collagen deposition [ 36 , 37 , 38 , 39 , 40 , 41 ]. Therefore, together with our previous investigation [ 15 , 16 , 19 , 41 , 42 , 43 ], these results show that blue-LED-light irradiation induces a quicker healing process.…”
Section: Discussionsupporting
confidence: 85%
“…Some authors have recently reported observations of an improved healing process when superficial wounds are treated with blue LED light with wavelengths in the range 410–430 nm, and a study in an animal model indicated that blue light led to a faster healing process in superficial lesions, with fibroblasts and myofibroblasts playing an important role [ 19 ]. After a critical literature review [ 22 ], further analyses of this group focused on the effects of blue light on fibroblasts and keratinocytes; it was observed that blue LED light may be used to modulate the metabolism and proliferation of human fibroblasts, and its effects on wound healing seemed to be particularly evident when studying fibroblast and keratinocyte co-cultures [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research showed that phototherapy based on blue light has produced beneficial consequences such as treatment of neonatal jaundice ( 123 125 ), regulation of melatonin and circadian rhythm ( 126 128 ), anti-inflammation ( 129 – 131 ), immunomodulation ( 132 ), wound healing ( 133 135 ), tissue regeneration, and anticancer therapies ( 103 , 114 , 133 , 136 ). Furthermore, blue light reduced the follicular colonization of Propionibacterium acnes by activating the endogenous bacterial porphyrin and inhibiting acne development, while possibly interfering with lipogenesis in adipocytes and suppressing sebum formation for acne treatment ( 137 ).…”
Section: Blue Light Photobiomodulation Therapy In Cancer Treatmentmentioning
confidence: 99%